Myocardial Hydatid Cyst in a Young Male Patient Who Feeds Pet at Home: A Case Report - Sinan Demirtas; Celal Yavuz; İsmail Basyigit; Ugur Firat; Ahmet Caliskan (Case Reports in Vascular Medicine)
Hydatid cysts are rarely asymptomatic depending on their location. Complaints may be only relevant due to secondary problems. This paper presents a case report of a myocardial hydatid cyst which was totally excised under cardiopulmonary bypass operation with median sternotomy. Patient was admitted to the hospital with complaint of atypical chest pain in pungent manner together with shortness of breath. Various methods are used for diagnosis. However, echocardiography and computerized tomography with contrast are usually enough for definitive diagnosis and for deciding the strategy of operation. Curative excision must be performed. Extra care should be provided during the operation in order to prevent contamination. Postoperative appropriate antibiotherapy must be administered. Environment should be changed, and infrastructure must be improved in order to prevent further recurrences.